ASMA BARLAS DAN GENDER PERSPEKTIF DALAM PEMBACAAN ULANG QS. AN-NISA/4:34 - Nuril Fajri (IAIN Manado, 2019)
AbstractGender discussion will always seem appealing from an Islamic perspective. Before Islam came, the pattern of life of Arab society was very prone to social conflict. Islam came to improve the human life with the spirit of justice, liberation, anti-oppression, and anti-discrimination. The culture of patriarchy that was once heavily rooted turned out to affect on the interpretation of Qur'anic verses done by the mufassirūn (Comentators on the Qur’an), especially during the Classic era, the interpretation ignored the Women's interests, so the difference between men and women is very noticeable. Islam recognizes the distinction but does not make it a discrimination. This can be seen from the perception and review of women such as women are considered weak, passive, more precious than men, emotional, and so forth. While in the study of religion, women are always used as the weak in various fields, such as of the concept of nusyudz, polygamy, witness adultery, inheritance treasures, reward and threats of torment, Shari'ah and so forth. In this case, through her concept of